How the biophilic design social movement informs planning, policy and professional practice - Soderlund, Jana; Newman, Peter (Springer Nature, 2022)
Background A new social movement called biophilic design has emerged over recent decades to enable greater connection between nature and urban populations to make biodiversity and natural systems a part of daily life in cities. Understanding the origins of this social movement can inform further progression, implementation and planning of biophilic design.